2015
DOI: 10.1002/nau.22921
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety and depression associated with urinary incontinence. A 10‐year follow‐up study from the Norwegian HUNT study (EPINCONT)

Abstract: Aims: Firstly, to investigate the association between depression, anxiety and urinary incontinence (UI) in a 10-year longitudinal study of women. Secondly, to investigate the association between possible differences in the stress-and urgency components of UI and different severities of depression and anxiety by age groups. Methods: In a longitudinal, population-based survey study, the EPINCONT part of the HUNT study in Norway, we analyzed questionnaire data on UI, depression and anxiety from 16,263 women from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 33 publications
7
82
0
4
Order By: Relevance
“…The presence of urgency incontinence at baseline increased the odds of developing anxiety at 10 years, and conversely the presence of anxiety at baseline increased the odds of developing urgency incontinence at 10 years in a Norwegian study. 12 Bidirectional temporal relationship was also observed in a one-year longitudinal study from the UK. 22 Fifth, successful management of OAB symptoms with medications reduced the anxiety symptoms.…”
Section: Commentmentioning
confidence: 78%
See 1 more Smart Citation
“…The presence of urgency incontinence at baseline increased the odds of developing anxiety at 10 years, and conversely the presence of anxiety at baseline increased the odds of developing urgency incontinence at 10 years in a Norwegian study. 12 Bidirectional temporal relationship was also observed in a one-year longitudinal study from the UK. 22 Fifth, successful management of OAB symptoms with medications reduced the anxiety symptoms.…”
Section: Commentmentioning
confidence: 78%
“…The developers of the HADS have recommended these cut-off points for mild (8–10), moderate (11–14), and severe (15–21) anxiety, 10,11 and recent studies have adopted these cut-offs. 12 To quantify the severity of anxiety symptoms, we have also analyzed the HADS-A data as a continuous variable (HADS-A range 0 to 21).…”
Section: Methodsmentioning
confidence: 99%
“…Parity is the one of the most important risk factors of UI and several previous studies reported that increasing parity was associated with increased risk of UI [13,15,25] . The effect of parity on UI may be related to the development of pelvic muscle atrophy and the impairment in the pelvic muscle nerves during birth [13,25] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of parity on UI may be related to the development of pelvic muscle atrophy and the impairment in the pelvic muscle nerves during birth [13,25] . Episiotomy or spontaneous vaginal tear and the use of forceps or vacuum for extraction in vaginal delivery may also lead to SUI over the years [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of physical activity in an attempt to manage/control the condition may also have an effect on overall health by increasing the risk of conditions such as hypertension [14, 15]. In addition, UI is also associated with poorer mental health among older persons including anxiety disorders [16] and depression [16, 17]. …”
Section: Introductionmentioning
confidence: 99%